Acaricide efficacy against a Brazilian Rhipicephalus (Boophilus) microplus isolated field population over a five-year period - RAYNAL, JOSÉ TADEU; Raynal, José Tadeu; LOPES BASTOS, Bruno; CAMPANHARO BAHIENSE, THIAGO; MEYER, ROBERTO; WAGNER PORTELA, RICARDO (Pubvet, 2020)
Abstract. The resistance of Rhipicephalus (Boophilus) microplus to acaricides is a concern. We evaluated an isolated population of the Brazilian semi-arid region during a period of five years. Significant variations in the efficacy of the acaricides studied were correlated with historical patterns of use, which varied significantly over the period.